(untitled) (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2020)
The aim of the study was to evaluated the effect of giving water hyacinth and fish oil in quail diet on the performance, egg cholesterol and egg fatty acid profile. This study used 200 unsex day old quail divided into 5 treatments and 4 replications that were reared 5 weeks and then selected male or female. The results of sexing quail at week 5 were 95 females and 86 males. Growth period diets (0-5 weeks) contains 24% crude protein and metabolic energy of 2900 kcal kg-1 and production period diets (5-12 weeks) contains 22% crude protein and 2900 kcal kg-1. The experimental design used a completely randomized design with the treatment of using water hyacinth that was 0%,1%, 2%, 3 % and 4% with fish oil which was 0%, 4%, 5%, 6% and 7% in quail diet. The variables measured were quail performance (0-5 week age and 5-12 week age), egg cholesterol, and egg fatty acid profile. The results showed that using of water hyacinth meal 1% -4% and fish oil 4%-5% in the diet of the growth period resulted in higher feed consumption and body weight gain than diet without water hyacinth and fish oil but feed conversion rasio were same. Quail performance of the production period was not affected by all treatments. Unsaturated fatty acids tend to increased in quail eggs. The lowest cholesterol level of quail eggs was by giving 2% of water hyacinth meal and 5% of fish oil in the diet. It was concluded that water hyacinth can be used as local feed ingredients in quail diet until 4%. Key words: Coturnix coturnix japonica, egg cholesterol, egg fatty acid profile, performance, production DAFTAR PUSTAKA Aboul-Enein AM, Al-Abd A, Shalaby EA, Abul-Ela F, Nasr-Allah AA & Mahmoud AM. 2011. Eichornia crassipes (MarT) solm. Plant Signal Behaviour. 6(6): 834-836 Afrose S, Hossain MS & Tsuji H. 2010. Effect of dietary karaya saponin on serum and egg yolk cholesterol in laying hens. British Poultry Science. 51 (6) : 797-804 Adeyemi OA, Adekoya JA & Abayomi R. 2012. Performance of broiler chickens fed diets containing cassave leaf: blood meal mix as replacement for soybean meal. Revista Cientifica UDO Agricola. 12 (1): 212-219 Aziz Z, Cyriac S, Beena V & Philomina PT. 2012.Comparison of cholesterol content in chicken, duck and quail eggs. Journal Veterinary Animal Science. 43: 64-66 Bragagnolo N & Rodriguez-Amaya DB. 2003. Comparison of the cholesterol content of Brazilian chicken and quail eggs. Journal of food Composition and Analysis. 16(2): 147-153 Chimote MJ, Barmase BS, Raut AS, Dhok AP & Kuralkar SV.2009. Effect of supplementation of probiotic and enzymes on performance of Japanese quails. Veterinary World. 2 (6): 219-220 Damongilala LJ. 2008. Kandungan asam lemak tak jenuh minyak hati ikan cucut botol (Cenctrophorus sp) yang diekstraksi dengan cara pemanasan. Jurnal Ilmiah Sains. 8(2): 249-253 Grigorova S, Nikolova M, Penkov D & Gerzilov V. 2014. Egg yolk lipid change in Japanese given Tribulus terrestris extract. Bulgarian Journal of Agricultural Science. 20 (6) : 1472-1476 Guclu BK, Uyanik F & Iscan KM. 2008. Effect of dietary oil sources on egg quality, fatty acid composition of eggs and blood lipids in laying quail. South American Journal of Animal Science. 38 (2): 91-100 Hartoyo B, Irawan I & Iriyanti N. 2005. Pengaruh asam lemak dan kadar serat kasar yang berbeda dalam ransum broiler terhadap kandungan kolesterol, HDL dan LDL serum darah. Animal Production. 7(1):27-33. Hemid, AEA, El-Gawad AAH, El-Wardany I, El-Daly EF & El-Azeem NAA. 2010. Alleviating effect of some environmental stress factors on productive performance in Japanese quail 2.Laying performance. World Journal of Agricultural Science. 6(5): 517-524 Hilmi M, Sumiati & Astuti DA.2015. Egg production and physical quality in Coturnix coturnix japonica fed diet containing piperine as phytogenic feed additive. Media Peternakan. 38(3): 150-155 Kamely M, Torshizi MAK & Khosravinia H. 2016. Omega 3 enrichment of quail eggs: age, fish oil, and savory essensial oil. Journal of Agricultural Science and Technology. 18 (2): 347-359 Khairani, Sumiati & Wiryawan KG. 2016. Egg production and quality of quails fed diets with varying levels of methionine and choline chloride. Media Peternakan. 39 (1): 34-39 Kurniawan M, Izzati M & Nurchayati Y. 2010. Kandungan klorofil, karotenoid, dan vitamin C pada beberapa spesies tumbuhan akuatik. Buletin Anatomi dan Fisiologi. 18(1):28-40 Leeson S & Summers JD. 2005. Commercial Poultry Nutrition. Third Edition. Canada (CA): Nottingham University Pr. LiYX, Wang YQ, Pang YZ, Li JX, Xie XH, Guo TJ & Li WQ. 2011. The effect of crude protein level in diets on laying performance, nutrien digestibility of yellow quails. International Journal of Poultry Science. 10(2): 110-112 Malik AA, Aremu A, Ayanwale BA & Ijaiya. AT 2016. A Nutritional evaluation of water hyacinth (Eichhornia crassipes. Martius Solms-laubach) meal diets supplemented with Maxigrain* Enzyme for growing pulllets. Journal of Raw Material Research Nigeria. 10(2): 18-44 Mahmood M, Sial AR, Saima, Akram M, Pasha TN & Jabbar MA. 2014. Effect of dietary energy levels on growth performance and feed cost analysis in Japanese quail. Pakistan Journal of Zoology. 45(5): 1357-1362 Mangisah I, Tristiarti, Murningsih W, Nasoetion MH, Jayanti ES & Astuti Y. 2006. Kecernaan nutrien eceng gondok yang difermentasi dengan Aspergillus niger pada ayam broiler. Journal of Indonesian Tropical Animal Agricultural. 31 (2): 124-128 Maulana IT, Sukraso & Damayanti S. 2014 .Kandungan asam lemak dalam minyak ikan Indonesia. Jurnal Ilmu dan Teknologi Kelautan Tropis. 6(1): 121-130 Metwally AA, El-Gellal AM & El-Sawaisi SM. 2009). Effect of silymarin on lipid metabolism in rat. World Applied Sciences Journal. 6 (12): 1634-1637 Mona MH, Morsy AS & Hasan AM. 2013. Egg yolk cholesterol and productive performance of laying hens influenced by dietary crude fiber levels under drinking natural salin water. Journal of Animal and Poultry Production. 4(3): 161-176 Muhammad M, Peter S, James G & Wosilat A. 2015. Growth performance of growing quails (Coturnix japonica) fed graded levels of Neem. International Journal of Applied Research. 1(2): 04-07 NRC.1994. Nutrient Requirement of Poultry. 9th Edition. Wahington D.C (US): National Academy Odo BI & Nnadi AE. 2014. Growth response of quails (Coturnix coturnix japonica) to varying levels of cassava (Manihot esculenta) tuber meal as a replacement for maize (Zea mays). American Journal of Experimental Agricultural. 4(12): 1898-1903 Riswandi. 2014. Kualitas silase eceng gondok (Eichhornia crassipes) dengan penambahan dedak halus dan ubi kayu. Jurnal Peternakan Sriwijaya. 3(1): 1-6 Rusmana,D. 2007. Pengaruh substitusi minyak sawit oleh minyak ikan lemuru dan suplementasi vitamin E dalam ransum ayam broiler terhadap performans. Jurnal Ilmu Ternak. 7(2): 101-106 Saha S. & Ray AK. 2011. Evaluation of nutritive value of water hyacinth (Eichhornia crassipes) leaf meal in compound diets for rohu Labeo rohita (Hamilton, 1822) fingerlings after fermentation with two bacterial strains isolated from fish gut. Turkish Journal of Fisheries and Aquatic Science. 11: 199-207 Sastrodihardjo S, Suci DM & Cahyanto MN. 1998. Penggunaan Minyak Ikan Lemuru dan Minyak Kelapa Sawit dalam ransum terhadap Kandungan Asam lemak Omega 3 dan Omega 6 dalam Kuning Telur Ayam. Bogor (ID): Seminar Nasional Peternakan dan Veteriner. Penelitian dan Pengembangan Pertanian Savory CJ & Gentle MJ. 1976. Changes in food intake and gut size in Japanese quail in response to manipulation of dietary fibre content. British Poultry Science. 17(6): 571-580 Sotolu AO & Sule SO. 2011. Digestibility and performance of water hyacinth meal in the diets of African catfish (Clarias gariepinus BURCHELL, 1822). Tropical and Subtropical Agroecosystem. 14: 245-250 Sim JS, Kitts WD & Bragg DB. 1984. Effect of dietary saponin on egg cholesterol level and laying hen performance. Canadian Journal of Animal Science. 64: 97-98 Tyagi T & Agarwal M. 2017. Antioxidant properties and phenolic compound in methanolic extracts of Eichornia crassipes. Reserarch journal of Phytochemistry. 11(2): 85-89. Tolik D, Polawska E, Charuta A, Nowaczewski S & Cooper R. 2014.Characteristics of egg parts, chemical composition and nutritive value of Japanese quail eggs-a review. Folia Biological (Krakow). 62 (4): 287-292 Tunsaringkarn T, Tungjaroenchai W & Siriwong W. 2013. Nutrient benefits of quail (Coturnix coturnix japonica) eggs. International Journal of Scientific and Research Publications. 3(5): 1-8